The distribution of zooplankton in the southern ocean and its dependence on the circulation of water - Voronina, N. M. (Sarsia, 1968)
The distribution of zooplankton in the Southern Ocean depends on seasonal changes in quantity and on redistribution of the plankton by currents. In the upper 100 m the meridianal component of the current shifts the maxima of some species northwards from the divergence zone at a mean velocity of about 20 cm/sec. In the Antarctic convergence zone the water sinks at a mean velocity of 10.5 m/day. This brings about an increase of the total plankton amounting to about 3% per day. As the southward flow of deep water is very slow the transfer of plankton in this layer is negligible.
Keywords: Sørishavet; marin biologi; oseanografi; plankton

Norsk ekspedisjon til Antarktis (Polarboken, 1968)
Keywords: Dronning Maud Land; ekspedisjoner

Ny øy ved Deception (Polarboken, 1968)
Keywords: Sørishavet; geofysikk

Antarktistraktaten, territorialkravene, forskningssamarbeidet - Bolin, Fredrik Th. (Polarboken, 1968)
Keywords: Antarktis; forskning; jus; politikk

Erobringen av Antarktis. Spredte glimt fra hvalfangstens historie - Brøther, Dagfinn (Teknisk ukeblad : Norges fremste på teknologi, 1968)
Keywords: Sørishavet; historie; hvalfangst; hvalfangstnæring; pelagisk

Morphology and distribution of the marine centric diatom Thalassiosira antarctica Comber - Hasle, Grethe R; Heimdal, Berit R (Journal of the Royal Microscopical Society, 1968)
Keywords: Sørishavet; diatomeer; fytoplankton; marinbiologi; plankton

Folkerettslige spørsmål vedrørende suverenitetsspørsmål i Antarktis - Krogdahl, Trygve (Internasjonal politikk, 1968)
Keywords: Antarktis; jus; politikk

De første fossiler av landvirveldyr oppdaget i Antarktis - Lund, Thoralv (Polarposten, 1968)
Keywords: Antarktis; paleontologi

Mennesket i kamp mot naturkreftene: slaget om Antarktis - Lund, Thoralv (Polarposten, 1968)
Keywords: Antarktis; stasjoner

Studies of surface snow at Plateau station - Lunde, Torbjørn (Antarctic Journal of the United States, 1968)
Keywords: Dronning Maud Land; ekspedisjoner; firnsnø; forskning; glasiologi; metamorfologi; morfologi; snø; stratigrafi

Studies of surface snow at Plateau Station - Orheim, Olav (Antarctic Journal of the United States, 1968)
Keywords: Dronning Maud Land; glasiologi; snø; stratigrafi

Amerikansk forskningsskip klargjøres for Antarktis-tur - Schroth, Charles S. (Polarboken, 1968)
Keywords: Antarktis; teknologi

Arktis og Antarktis : aktuelle problemstillinger - Sollie, Finn (Internasjonal politikk, 1968)
Keywords: Antarktis; Antarktistraktaten; polarområdene; politikk; utforskning; vitenskap

I telt på evig is: norsk polarekspedisjon til sydpollandet - Torkildsen, Torbjørn (Nå, 1968)
Keywords: Antarktis; Dronning Maud Land; ekspedisjoner; forskning; politikk

Norsk polarekspedisjon til sydpollandet: i telt på evig is - Torkildsen, Torbjørn (Nå, 1968)
Keywords: Dronning Maud Land; ekspedisjoner

Hvorfor døde Scott? - Zapffe, Peter Wessel (Polarboken, 1968)
Keywords: Antarktis; ekspedisjoner; historie